Use of silicone implants in reconstructive plastic surgery for breast cancer - D. D. Pak; E. A. Rasskazova (ABV-press, 2014)
The paper considers procedures for reconstructive plastic operations, by using silicone implants, in patients with breast cancer. It analyzes 592 primary breast repairs and evaluates their aesthetic effects and complications. The surgical procedures are described.